Split Suckling, Birth Order, and Birth Weight Affects Colostrum Intake and Pre-Weaning Weight Gain - J. Morton; A. Langemeier; T. Rathbun; D. L. Davis (Kansas Agricultural Experiment Station Research Reports, 2017)
Thirty sows (DNA Line 241, n = 10/treatment) and litters (sired by Line 600, pigs n = 412) were used to determine the effects of split suckling on immunocrit, colostrum intake, and growth of low birth weight pigs and pigs that farrow last in the birth order. Three treatments were used 1) control, all pigs suckled ad libitum; 2) weight based, the heaviest 6 pigs were removed for 1.5 h; or 3) birth order based, the first half of the litter was removed for 1.5 h. Over all litters, heavier pigs at birth had greater (P<0.01) colostrum intake and pigs born in the last half of the litter had lower (P<0.01) immunocrits (a measure of circulating immunoglobulins) than pigs born in the first half of the litter. Removing the heaviest 6 pigs for 1.5 h beginning 6 h after farrowing resulted in increased (P<0.05) weight gain by d 7. A tendency (P = 0.15) for treatment × birth order interactions suggests that split suckling increased colostrum intake for the later born pigs.
Keywords: colostrum intake; low birth weight pigs; split suckling